2021
DOI: 10.1371/journal.pone.0256741
|View full text |Cite
|
Sign up to set email alerts
|

The potential for diversion of prescribed opioids among orthopaedic patients: Results of an anonymous patient survey

Abstract: Introduction Diversion of prescription opioid medication is a contributor to the opioid epidemic. Safe handling practices can reduce the risk of diversion. We aimed to understand: 1) if orthopaedic patients received instructions on how to safely handle opioids, 2) their typical storage/disposal practices, and 3) their willingness to participate in an opioid disposal program (ODP). Methods Cross-sectional study of adult orthopaedic patients who completed an anonymous survey on current or past prescription opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Studies have also shown that patients do not receive adequate education in regards to opioids. Sundararajan et al [ 28 ] surveyed 569 patients who received an opioid script and found that just 44% received storage instructions, just 56% received disposal instructions, and a high percentage reported having unused opioids that were not properly disposed of. These numbers indicate a need for improved provider and patient education with regards to opioid medications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that patients do not receive adequate education in regards to opioids. Sundararajan et al [ 28 ] surveyed 569 patients who received an opioid script and found that just 44% received storage instructions, just 56% received disposal instructions, and a high percentage reported having unused opioids that were not properly disposed of. These numbers indicate a need for improved provider and patient education with regards to opioid medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, opioids are associated with potential harms, including risks of long-term use, negative surgical outcomes and potential diversion. [17][18][19][20][21] US and Canadian studies have reported that about 10% of patients undergoing surgery are persistent opioid users within 1 year of surgery 18 22 and that surgical patients generally use less opioids than prescribed, with the potential for diversion for non-medical use. 23 Recognising these potential harms, initiatives and interventions to address the opioid crisis have mainly focused on regulatory changes for prescription opioids for chronic pain, with less clear guidelines/recommendations for postoperative opioid therapy.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…47,48 Additionally, patients should be educated on safe storage and disposal practices to avoid potential narcotic diversion and abuse. 49 Finally, a key component of preoperative counseling is setting reasonable patient expectations regarding analgesia. While we strive to provide the safest and most effective pain management strategies, pain is a "normal" aspect of recovery from shoulder surgery.…”
Section: Strategiesmentioning
confidence: 99%